Management preference of deep carious lesion in permanent mature teeth among dentists in Riyadh city - Afra H Elrashid; Nada A Alsulaiman; Alanoud M Alqahtani; Farah M Algholamy; Abdulaziz M Alobaida (Wolters Kluwer Medknow Publications, 2022)
Introduction: The management of deep caries lesion can be accomplished by complete caries excavation, partial caries removal, and stepwise excavation techniques. Dentists do not agree on a single management due to available evidence about the effectiveness of different treatment options of deep carious lesion that are inconsistent. Aim: The aim is to investigate the attitude and behavior of management preference of deep caries in mature permanent teeth among dentists in Riyadh city. In addition, to compare these findings with academic standards, World Dental Federation and International Caries Consensus cooperation (ICCC). Materials and Methods: A randomized cross-sectional study was conducted in which 540 questionnaires were distributed to dentists in Riyadh city. The questionnaire included four clinical scenarios to investigate the participant's attitude and behavior of management preference of deep carious lesion of permanent teeth in Riyadh city in 2019. Results and Discussion: Response rate was 74%. Findings illustrate that 86.8% of participants preferred complete caries excavation in case of deep caries with no pain nor risk of pulpal exposure. 41.3% of the participants preferred complete caries excavation in case of deep caries with no pain but risk of pulpal exposure presence. 64.8% participants preferred complete caries excavation in case of deep caries with pain on provocation and no risk of pulpal exposure. 58.3% participants preferred root canal treatment in case of deep caries with pain on provocation and with risk of pulpal exposure. About 76.80% of participants believed that after 2 years from complete caries removal, a high success rate (more than 80%) will result. Conclusion: The majority of participants prefer more invasive approaches in the treatment of deep carious lesions and unaware of the minimally invasive dentistry.